What are the Crucial Factors in Gaining Customer Recommendations in the Airline Industry? - Dalianus Riantama (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The airline business is continually growing. This study tries to find out important factors for customers to give their recommendations for an airline. Text mining approach and feature selection methods are applied to clean the data set and to select the most crucial factors of customer recommendations. This study collected 846 online customer reviews for full-service airlines and 179 low-cost carrier airlines. Cleanliness and crew care are the most critical factors for full-service airline customers. Low-cost carrier airline customers were more concerned about the value of money and flight information. The results provide airlines’ managers with new insights to make their customers willing to give recommendations and gain a positive brand image. Keywords: Online customers review, text mining, customer recommendations, feature selection, airline